2018
DOI: 10.1002/mnfr.201801029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2‐Thiothiazolidine‐4‐Carboxylic Acid, a Common Metabolite of Isothiocyanates, as a Potential Biomarker of Cruciferous Vegetable Intake

Abstract: Scope Cruciferous vegetable consumption is associated with favorable health outcomes. Bioactive compounds arising in these, especially isothiocyanates, exert effects that contribute to prevention of disease, in large part through the attenuation of inflammation and oxidative stress. However, much about isothiocyanate metabolites and their role as biomarkers of crucifer intake remain unknown. Methods and results The utility and limitations of 2‐thiothiazolidine‐4‐carboxylic acid (TTCA) as a urinary biomarker of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The Arabidopsis cell wall irx1-6 mutant shows high resistance to pathogens and presents high endogenous concentrations of raphanusamic acid (Sanchez-Vallet et al 2010) ( Table 1). Different Cruciferous plants produce concentrations of endogenous raphanusamic acid (50-150 μM) before and after pathogen attack (Bednarek et al 2011, Palliyaguru et al 2019 (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The Arabidopsis cell wall irx1-6 mutant shows high resistance to pathogens and presents high endogenous concentrations of raphanusamic acid (Sanchez-Vallet et al 2010) ( Table 1). Different Cruciferous plants produce concentrations of endogenous raphanusamic acid (50-150 μM) before and after pathogen attack (Bednarek et al 2011, Palliyaguru et al 2019 (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Others studied the effect of alcohol on urinary excretion of the disulfide, 2-thiothiazolidine-4-carboxylic acid (TTCA), among non-exposed subjects, and showed that high liquor intakes (150–250 mL) may interfere with the levels of urinary TTCA [ 264 ]. However, TTCA levels have also been proposed to reflect crucifer intake [ 265 ]. In some other studies, spirits, and distillates have been used with the aim to identify general markers for alcohol consumption (e.g., PEth, EtG, FAEE) and not for finding specific intake biomarkers of spirits or distillates [ 131 , 266 270 ].…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, a 5-day washout period was implemented, followed by a second 7-day drinking period (beverage rich in SFN). The authors hypothesized that this assay would allow the evaluation of the bioavailability of SFN and its mercapturic derivatives by measuring TTCA in urine as a common isothiocyanate-derived metabolite, with the potential to be used as a biomarker of the intake of cruciferous vegetables ( Table 2 ) [ 68 ]. As the main conclusion of this work, TTCA, which seems to be produced by all crucifers, regardless of the identity of the GSL/ITC precursor, provided the opportunity to quantify the intake and absorption of organosulfur compounds from any cruciferous vegetable.…”
Section: Dietary Interventions With Cruciferous Sproutsmentioning
confidence: 99%
“…As the main conclusion of this work, TTCA, which seems to be produced by all crucifers, regardless of the identity of the GSL/ITC precursor, provided the opportunity to quantify the intake and absorption of organosulfur compounds from any cruciferous vegetable. Indeed, the authors observed increases of up to 60% in the urine concentration of TTCA 12 h after the ingestion of GR and SFN beverages [ 68 ]. In addition, further measurements showed that much of the TTCA detected in the human urine was formed in the broccoli beverages before consumption, although in beverages with a high SFN content, some additional TTCA was formed as a result of SFN biotransformation.…”
Section: Dietary Interventions With Cruciferous Sproutsmentioning
confidence: 99%
See 1 more Smart Citation